PENINGKATAN MEKANISME KOPING PADA PASIEN KANKER PAYUDARA DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Tati Murni Karokaro; Rahmad Gurusinga; Dian Anggriyanti; Rosita Ginting; Mila Gustia; Mif Zannah; Abdi Lestari Sitepu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
The success of the coping mechanism in patients with breast cancer depends not only on early detection but also an understanding of the mechanisms that cause it. Psychological impact experienced by each patient, especially breast cancer which underwent different treatment depending on the level of severity (stage). The differences before and after being given education can affect the coping mechanism of the individual itself. One of the conditions that can cause anxiety is the process of implementing chemotherapy treatment. The purpose of this study was to determine the increase in coping mechanisms in breast cancer patients at Grandmed Lubuk Pakam Hospital. Counselling was carried out to see an increase in coping mechanisms, namely by directly informing breast cancer patients about coping mechanisms with education, distributing leaflets and analyzing data before and after education. Data analysis was performed using the Paired Sample T-Test with a confidence level of 95% and a value of Î± = 0.05. The results obtained from this study have shown a change in the coping mechanism of the patient before and after being given education on the application of the coping mechanism with a p-value = 0.001 (Î±> 0.05). In conclusion, there is an increase in coping mechanisms in breast cancer patients who are carried out according to standards, for health institutions there is a need for supervision and counselling to the public about the importance of maintaining health, especially for breast cancer patients at Grandmed Lubuk Pakam Hospital.